2020
DOI: 10.1038/s41380-020-0829-y
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation as measured by positron emission tomography in patients with recent onset and established schizophrenia: implications for immune pathogenesis

Abstract: Positron emission tomography (PET) imaging of the 18 kDa translocator protein (TSPO), which is upregulated in activated microglia, is a method for investigating whether immune activation is evident in the brain of adults with schizophrenia. This study aimed to measure TSPO availability in the largest patient group to date, and to compare it between patients with recent onset (ROS) and established (ES) schizophrenia. In total, 20 ROS patients (14 male), 21 ES (13 male), and 21 healthy controls completed the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 38 publications
1
44
0
Order By: Relevance
“…More directly, a number of positron emission tomography (PET) studies in patients at various stages of schizophrenia now report no increase in radioligand binding to the translocator protein (TSPO), which is a biomarker for activated microglia 11 . Our recent study found that reductions in TSPO binding in schizophrenia, which we hypothesised, are an indication that microglia are in a non-inflamed phagocytic mode driven by astrogliosis 12 . These findings together with large scale transcriptomic evidence in postmortem brain, discussed below, suggest that microglial inflammation may not be central to pathogenesis in schizophrenia, hence the lack of efficacy of minocycline.…”
Section: Introductionmentioning
confidence: 75%
“…More directly, a number of positron emission tomography (PET) studies in patients at various stages of schizophrenia now report no increase in radioligand binding to the translocator protein (TSPO), which is a biomarker for activated microglia 11 . Our recent study found that reductions in TSPO binding in schizophrenia, which we hypothesised, are an indication that microglia are in a non-inflamed phagocytic mode driven by astrogliosis 12 . These findings together with large scale transcriptomic evidence in postmortem brain, discussed below, suggest that microglial inflammation may not be central to pathogenesis in schizophrenia, hence the lack of efficacy of minocycline.…”
Section: Introductionmentioning
confidence: 75%
“…A meta-analysis by Marques et al [48] of TSPO PET studies and microglial activation exposed a moderate effect on gray matter relative to other brain tissue in schizophrenia when using binding potential as an outcome measure but no difference when using volume of distribution as an outcome measure. The TSPO PET study by Conen et al [49] found no microglial activation in patients with recent onset and established schizophrenia compared with healthy control subjects in the ACC, PFC, parietal cortex, and brainstem, but significant changes in the thalamus and putamen.…”
Section: The Role Of Microglial Cells In Schizophreniamentioning
confidence: 97%
“…(2018) found that minocycline, a potent inhibitor of microglial inflammation, was ineffective in recent-onset patients. The findings were followed by meta-analyses of in vivo Positron Emission Tomography (PET) imaging, providing compelling evidence that the translocator protein TSPO (a putative biomarker for inflamed microglia) is not increased but reduced in psychosis ( Plavén-Sigray et al, 2018 , 2020 ), as we had observed in several brain regions of antipsychotic-free patients ( Conen et al., 2020 ). We proposed that microglia are driven into a non-inflamed synaptic pruning state by overactivity of TGF-β mediated astroglial restraint ( Conen et al., 2020 ).…”
Section: Tregs: Role In the Neuroimmune Network And Therapeutic Implicationsmentioning
confidence: 94%